Investigating Awareness Level and Attitudes Toward Induced Abortion in Patients Admitted to Medical Centers in Tehran, Iran - Najari, Fares; Najari, Dorsa; Fazleh Hashemi, Rana; Najari, Elsay (Archives of Men’s Health, 2023)
Background: Abortion is recognized as a social and cultural problem across societies, posing risks to people’s health. This study aims to explore various facets of induced abortion in patients admitted to medical centers in Tehran. Method: This descriptive-cross-sectional study surveyed referred patients at Mahdieh, Taleghani, and Shohada-e-Tajrish Hospitals in Tehran, Iran. Information was collected using a researcher-made questionnaire. Data were analyzed employing the chi-square test, t-test, and Pearson’s correlation coefficient, considering a P-value <0.05 as significant. Results: Among the 1,200 examined patients, 75% were in favor of induced abortion but within legal bounds (95%, CI=58-90). Furthermore, 65% of the participants demonstrated adequate knowledge about induced abortion and its associated side effects (95%, CI=55-75), yet they advocated it due to financial and welfare problems. Meanwhile, there was a statistically significant correlation between awareness scores and age, education, and gestational age (P-value<0.04). Conclusion: The awareness and attitude toward abortion vary among individuals. However, enforcing different severe restrictions and stringent abortion laws may lead to destructive consequences.